2021
DOI: 10.1177/13634607211013280
|View full text |Cite
|
Sign up to set email alerts
|

Queer expectations: An empirical critique of rural LGBT+ narratives

Abstract: Much of the body of literature on LGBT+ populations within the United States place urban areas and so-called gayborhoods as goals and eventualities, paralleling early US studies on immigration. Using a multistage, mixed-methods approach, consisting of secondary analysis of the Pew 2013 Study of LGBT Persons ( N = 1197) and in-depth interviews (35 gay men, 2 trans-identifying individuals, 1 heterosexual woman, and 2 lesbians), we found that rural LGBT+ residents engaged in both short-term and long-term travel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…Research shows that the context of discrimination and victimization matters, and that stressors impact individuals' mobility, health, and life chances (MUCF) -The Swedish Agency for Youth and Civil Society (2020). Some small rural communities can be restrictive toward Queer people, see Misgav and Hartal (2019) reporting the experiences of sexual minorities and their fight to the right to be different, while other rural areas can be inclusive and welcoming (Rosenberg 2021); see, for instance, Conner and Okamura (2021) who illustrate the advantages of living in rural areas for LGBTQ+ rights advocates.…”
Section: Reason 15 -Technology Can Become An Asset In Situational Rur...mentioning
confidence: 99%
“…Research shows that the context of discrimination and victimization matters, and that stressors impact individuals' mobility, health, and life chances (MUCF) -The Swedish Agency for Youth and Civil Society (2020). Some small rural communities can be restrictive toward Queer people, see Misgav and Hartal (2019) reporting the experiences of sexual minorities and their fight to the right to be different, while other rural areas can be inclusive and welcoming (Rosenberg 2021); see, for instance, Conner and Okamura (2021) who illustrate the advantages of living in rural areas for LGBTQ+ rights advocates.…”
Section: Reason 15 -Technology Can Become An Asset In Situational Rur...mentioning
confidence: 99%
“…In Sweden, MUCF (2020) found that young LGBTQ+ people in rural areas have less access to meeting places with other youths and may avoid attending recreational events and activities due to the fear of being treated badly. However, there are cases in which rural areas can be inclusive and welcoming (Rosenberg 2021); see for instance, the case of Conner and Okamura (2021) who list the advantages of living in rural areas for LGBTQ+ people.…”
Section: Discrimination and Hate Crimes Against Lgbtq+ Personsmentioning
confidence: 99%
“…Bell (2000), for instance, which is a seminal study on cultural constructions of rural gay masculinity in the United States, showed a blurred rural-urban divide. More recently, Conner and Okamura (2021) illustrated the advantages of living in rural areas for LGBTQ+ rights advocates, while DeKeseredy et al (2014) showed that the way the media has portrayed the sexuality of rural inhabitants in the United States (no matter their gender or sexual orientation) is distorted and serves the interests of particular rationalities of abuse. Missing in the current criminological research is a better understanding of why certain rural places impact positively on LGBTQ+ safety, while others, negatively.…”
Section: Gendering and Queering The Ruralmentioning
confidence: 99%